The Effect of Good Corporate Governance and Inflation on Financial Distress with Financial Performance as a Mediating Variable - Arsintya Dewi Wulandari; Nur Anisah (Proceeding International Conference on Digital Education and Social Science, 2025)
The purpose of this study is to examine how good corporate governance and inflation affect financial distress using financial performance as a mediating variable. This research focuses on companies that were listed between 2020 and 2024 in the Indonesia Stock Exchange's (IDX) apparel and luxury goods subsector. The methodology used in this study is quantitative. A final sample of 14 firms was chosen by purposive sampling from the 24 enterprises that made up the research population. Data testing and analysis were carried out using descriptive statistical tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), coefficient of determination tests (Adjusted R Square), and PROCESS Macro Hayes mediation tests using SPSS 27 software. The results show that good corporate governance has a positive and significant effect on financial performance, while inflation has a negative and significant effect on financial performance. In addition, good corporate governance has a positive and significant effect on financial distress, inflation has a positive and non-significant effect on financial distress, and financial performance has a negative and significant effect on financial distress. The mediation test shows that financial performance is unable to mediate the effect of good corporate governance on financial distress, but is able to mediate the effect of inflation on financial distress.